2022
DOI: 10.1155/2022/6557817
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Investigating Influences of Synthesizing Eco‐Friendly Waste‐Coir‐Fiber Nanofiller‐Based Ramie and Abaca Natural Fiber Composite Parameters on Mechanical Properties

Abstract: Clean technology-based natural fiber composite fabrication is the prime aim of this piece of research. Natural fibers highly replace metal usage in industries and automobile, marine, medical applications, and so on. Vast amounts of natural fibers are freely available in all areas. In this research, work nanofiller material such as nano form waste coir fiber is collected from used car seat. The 10 wt.% of nanofiller material is added to the preparation of natural nanocomposites (ramie and abaca fiber). Hybrid c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…Strojniški vestnik -Journal of Mechanical Engineering 69(2023)[7][8][339][340][341][342][343][344][345][346][347][348][349][350][351] …”
mentioning
confidence: 99%